An Urgency for Extraordinary Member to Take Tests to Fulfil the Requirements to be Notary Public Official - Dessy Agustina Harahap; Windy Sri Wahyuni (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
This research deals with an urgency for extraordinary member to take tests to fulfil the requirements to be notary public official. This type of research used in this study is normative legal research. The results shows that The extraordinary Members Tests of Indonesian Notary Association is only a formality aimed at introducing Statutes and bylaws of Indonesian Notary Association, Organizational Regulations and Composition of Indonesian Notary Association Management to prospective members who take the tests of extraordinary members. Because there is a formality, no tests participants do not pass as long as the tests follow the entire tests material. Therefore the Writers' team considers that the extraordinary member tests are more effective when they are turned into a seminar or training course because the basic objective is only to introduce the organization.